Preparation and in vitro/in vivo characterisation of a melt pelletised paracetamol/stearic acid sustained release delivery system. Issue 2 (2004) - Grassi Grassi, Mario Mario; Voinovich Voinovich, Dario Dario; Grabnar Grabnar, Iztok Iztok; Franceschinis Franceschinis, Erica Erica; Perissutti Perissutti, Beatrice Beatrice; Filipovic-Grcic Filipovic-Grcic, Jelena Jelena
Abstract : The potential of a sustained release formulation for paracetamol produced by melt pelletisation was investigated. After the production of the pellets, based on the combination of stearic acid as a melting binder and anhydrous lactose as a filler, the 3000–2000 μ m size fraction was selected in the light of the promising in vitro dissolution results for further characterisations, including scanning electron microscopy (SEM), X-ray photoelectron spectroscopy (XPS), specific surface area and true density determination. Hence the release mechanism was analysed with the help of an appropriate mathematical model. The mathematical model was built on the hypotheses that drug diffusion and solid drug dissolution in the release environment are the key phenomena affecting drug release kinetics. Bioavailability of the developed formulation was evaluated in an in vivo study in eight subjects.